One-pot Hydrothermal Fabrication of Carbon Nanodots From Natural Products for Multifaceted Applications - Naik, Gaurav Gopal (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: One-pot Hydrothermal Fabrication; Carbon Nanodots; Natural Products; Multifaceted Applications